Team Cognition as a Barrier and Facilitator in Care Transitions: Implications for Work System Design. (November 2019) - Wooldridge, Abigail R.; Carayon, Pascale; Hoonakker, Peter; Hose, Bat-Zion; Brazelton, Thomas B.; Eithun, Ben; Dean, Shannon M.; Kelly, Michelle M.; Kohler, Jonathan E.; Ross, Joshua C.; Rusy, Deborah; Gurses, Ayse P.
Inpatient care of pediatric trauma patients includes care transitions, including from emergency department (ED) to operating room (OR), OR to pediatric intensive care unit (PICU) and ED to PICU, which are important to patient safety and quality of care. Previous research identified work system barriers and facilitators in these transitions; the most common related to team cognition. We conducted interviews with 18 healthcare professionals to better understand how work system design influences team cognition barriers and facilitators. Using Systems Engineering Initiative for Patient Safety (SEIPS)-based process modeling, we identified when each barrier/facilitator occurred. The ED to OR transition had more barriers in transition preparation, while OR to PICU had more facilitators in the transition. Future research should explore solutions to support team cognition early in the ED to OR transition, such as designing a technology to be used by distributed teams.